Differences in peripheral immune system gene expression in frontotemporal degeneration. Issue 3 (21st January 2022) - Sawyer, Russell P.; Hill, Emily J.; Yokoyama, Jennifer; Medvedovic, Mario; Ren, Yan; Zhang, Xiang; Choubey, Divaker; Shatz, Rhonna S.; Miller, Bruce; Woo, Daniel
Abstract : Abstract: The peripheral immune system has a key pathophysiologic role in Frontotemporal degeneration (FTD). We sought a comprehensive transcriptome-wide evaluation of gene expression alterations unique to the peripheral immune system in FTD compared to healthy controls and amyotrophic lateral sclerosis.Nineteen subjects with FTD with 19 matched healthy controls and 9 subjects with amyotrophic lateral sclerosis underwent isolation of peripheral blood mononuclear cells (PBMCs) which then underwent bulk ribonucleic acid sequencing. There was increased expression in genes associated with CD19 + B-cells, CD4 + T-cells, and CD8 + T-cells in FTD participants compared to healthy controls. In contrast, there was decreased expression in CD33 + myeloid cells, CD14 + monocytes, BDCA4 + dendritic cells, and CD56 + natural killer cells in FTD and healthy controls. Additionally, there was decreased expression is seen in associated with 2 molecular processes: autophagy with phagosomes and lysosomes, and protein processing/export. Significantly downregulated in PBMCs of FTD subjects were genes involved in antigen processing and presentation as well as lysosomal lumen formation compared to healthy control PBMCs. Our findings that the immune signature based on gene expression in PBMCs of FTD participants favors adaptive immune cells compared to innate immune cells. And decreased expression in genes associated with phagosomes and lysosomes in PBMCs of FTD participants compared to healthy controls. Abstract : Supplemental Digital Content is available in the text